Tanggung Jawab Pemerintah Dalam Penyelenggaraan Kesehatan Mental - Kusumaningsih, Rila (Jurnal Ilmu Sosial dan Humaniora, 2023)
The right to mental health is an integral part of the right to health with the main responsibility for fulfilling it is the obligation of the state according toestablished right. The government as a tool of the state has an obligation to be responsible for the implementation of mental health efforts for its citizens. However, if you look atthe current condition of access to mental health services in Indonesia still does not meet the need for health services which are the responsibility of the government, such as the lack of quality, equitable and affordable health services. This study aims to find out more regarding the government's responsibility for community mental health and efforts to implement mental health. The research method used in this study is an empirical juridical research. This research will be conducted with an empirical approach supported by normative data. Based on the research that has been done An optimal strategy needs to be implemented for each individual, family and community with a comprehensive, integrated and sustainable promotive, preventive, curative and rehabilitative approach as an effort to tackle mental health in Indonesia